Atypical spatial frequency dependence of visual metacognition among schizophrenia patients - Ai Koizumi; Tomoki Hori; Brian Maniscalco; Makoto Hayase; Ryou Mishima; Takahiko Kawashima; Jun Miyata; Toshihiko Aso; Hakwan Lau; Hidehiko Takahashi; Kaoru Amano (NeuroImage: Clinical, 2020)
Although altered early stages of visual processing have been reported among schizophrenia patients, how such atypical visual processing may affect higher-level cognition remains largely unknown. Here we tested the hypothesis that metacognitive performance may be atypically modulated by spatial frequency (SF) of visual stimuli among individuals with schizophrenia, given their altered magnocellular function. To study the effect of SF on metacognitive performance, we asked patients and controls to perform a visual detection task on gratings with different SFs and report confidence, and analyzed the data using the signal detection theoretic measure meta-d′. Control subjects showed better metacognitive performance after yes- (stimulus presence) than after no- (stimulus absence) responses (‘yes-response advantage’) for high SF (HSF) stimuli but not for low SF (LSF) stimuli. The patients, to the contrary, showed a ‘yes-response advantage’ not only for HSF but also for LSF stimuli, indicating atypical SF dependency of metacognition. An fMRI experiment using the same task revealed that the dorsolateral prefrontal cortex (DLPFC), known to be crucial for metacognition, shows activity mirroring the behavioral results: decoding accuracy of perceptual confidence in DLPFC was significantly higher for HSF than for LSF stimuli in controls, whereas this decoding accuracy was independent of SF in patients. Additionally, the functional connectivity of DLPFC with parietal and visual areas was modulated by SF and response type (yes/no) in a different manner between controls and patients. While individuals without schizophrenia may flexibly adapt metacognitive computations across SF ranges, patients may employ a different mechanism that is independent of SF. Because visual stimuli of low SF have been linked to predictive top-down processing, this may reflect atypical functioning in these processes in schizophrenia.